2004
DOI: 10.5713/ajas.2004.1729
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Enzyme Complex Supplementation on Growth, Ileal and Apparent Fecal Digestibility and Morphology of Small Intestine in Pigs

Abstract: A total of 140 weaning pigs were used to determine the effects of digestive enzyme supplementation to corn-soybean meal diets on growth performance, physiological changes of small intestine, microorganisms and pH in the gastrointestinal tract. Two kinds of enzyme complex (A, B) were used in this experiment. Pigs were allotted in a completely random design (CRD) to five replicates with four pigs per pen. Diets and water were provided for ad libitum consumption. Treatments included 1) Control: without enzyme sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…These results concur with data reported by Willamil et al (2012), who observed an improvement in VH and VH:CD, and decrease in CD of the ileum of growing pigs fed wheat-based diets supplemented with a carbohydrase complex. Contrary to the present results, however, Kim et al (2004) reported that there were no effects of multienzyme preparation on the VH and CD in the duodenum, jejunum, and ileum of weaned pigs fed a corn-SBM-based diet. Willamil et al (2012) also observed no effects of a carbohydrase complex on ileal VH and CD of pigs fed a corn-SBM diet.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results concur with data reported by Willamil et al (2012), who observed an improvement in VH and VH:CD, and decrease in CD of the ileum of growing pigs fed wheat-based diets supplemented with a carbohydrase complex. Contrary to the present results, however, Kim et al (2004) reported that there were no effects of multienzyme preparation on the VH and CD in the duodenum, jejunum, and ileum of weaned pigs fed a corn-SBM-based diet. Willamil et al (2012) also observed no effects of a carbohydrase complex on ileal VH and CD of pigs fed a corn-SBM diet.…”
Section: Discussioncontrasting
confidence: 99%
“…Exogenous enzymes have been successfully used in the pigs industry to minimize or eliminate the negative effect of antinutritional factors, to stimulate nutrient digestibility and improve nutritive values of high non-starch polysaccharides (NSP) containing feedstuff such as wheat, oats, barley, and rye (Willamil et al 2012;Kianfar et al 2013;Karimi & Zahedi 2015). However, it is thought that feedstuff like corn and SBM may not benefit from exogenous enzyme supplementation due to lower level of soluble NSP and lesser viscosity (Kim et al 2004;Willamil et al 2012). Corn contains 10-11% NSP, which are mainly arabinoxylan and β-galactomannan, and SBM contains 22.7% NSP such as αgalactosides [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the effects of enzyme supplementation on performance or nutrient digestibility of pigs fed corn-based diets, as reported in literature, are not consistent. Some studies show positive responses to enzyme supplementation (Jakob et al, 2005a;Fang et al, 2007;Ji et al, 2008), but others fail to show any effects (Li et al, 1999;Kim et al, 2004). Gorn contains approximately 7 to 9% NSP, mainly insoluble arabinoxylans (Dierick and Decuypere, 1996;Summers, 2001), whereas soybean meal contains approximately 3% soluble NSP and 16% insoluble NSP (Irish and Balnave, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…Lower enzyme activity of exogenous carbohydrases in the gastrointestinal tract may be a reason for the lack of effects of the supplemental enzyme on the energy digestibility ( Kim et al, 2004 ). The β-mannanase (mannan-endo-1,4-β-D-mannosidase, EC 3.2.1.78) product used in this study was an endo-acting carbohydrase, attacking the 1,4-β-D-mannan main chain of the mannan compounds and releasing mannan-oligosaccharides or a small amount of mannose ( McCleary, 1988 ; Kong et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%